Digital Economic Transformation and its Implications for Monetary Economic Policy in Indonesia - David Chandra; Lia Nazliana Nasution (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of digital economic transformation on inflation in Indonesia. The indicators of digital economic transformation examined in this study include internet penetration, digital transactions/e-commerce, the use of digital financial services, national digital economic value, and digital financial infrastructure. This research employs a quantitative approach with an associative research design. The data used are secondary time-series data covering the period 2019–2024, obtained from the Central Bureau of Statistics (BPS), Bank Indonesia, the Financial Services Authority (OJK), the Ministry of Communication and Information Technology, as well as reports from the World Bank and Google–Temasek–Bain. The analytical method applied is multiple linear regression. The results show that, partially, internet penetration has a negative and significant effect on inflation, indicating that increased internet access enhances market efficiency and contributes to lower inflation. In contrast, digital transactions/e-commerce have a positive and significant effect on inflation, reflecting increased consumer demand through digital platforms. Meanwhile, the use of digital financial services, national digital economic value, and digital financial infrastructure do not have a significant effect on inflation. Simultaneously, the variables of digital economic transformation do not significantly affect inflation. The adjusted R-square value of 0.519 indicates that the model explains 51.9 percent of inflation variation, while the remaining variation is influenced by other macroeconomic factors.